The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1980-5373-mr-2020-0344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Alumina Supported Palladium Catalyst on the Magnesium Sulfate Decomposition Kinetics

Abstract: The sulfur related thermochemical water-splitting cycles are an important class of chemical processes considered for hydrogen production. Recently, the magnesium sulfate thermal decomposition has been reported as a potential unit operation in one of these cycles. Therefore, some interest has been observed in the use of catalysts to lower the activation energy of such reactions. In this context, the present manuscript reports the thermodynamics and kinetics modeling results associated with this reaction system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For each analysis, the modeling quality was determined by the value of the correlation coefficient (R 2 ) calculated for each dataset. This methodology was recently successfully applied for the thermal decomposition modeling of MgSO 4 [40] and potassium alum [46] reaction systems.…”
Section: Thermogravimetric Analysis and Kinetic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…For each analysis, the modeling quality was determined by the value of the correlation coefficient (R 2 ) calculated for each dataset. This methodology was recently successfully applied for the thermal decomposition modeling of MgSO 4 [40] and potassium alum [46] reaction systems.…”
Section: Thermogravimetric Analysis and Kinetic Modelingmentioning
confidence: 99%
“…In the work of Mello et al [40], who also used the Pd/Al 2 O 3 catalyst, it was observed that palladium tended to oxidize and initiate the formation of PdO up to approximately 900 • C in the reaction system and then dissociate, returning to the metallic form at higher temperatures. According to O'Keefe et al [54] and Barbarossa et al [17], the oxide's catalytic activity forms in the decomposition of sulfur trioxide.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…All the calculations were made using Python 3.8.2. This methodology was recently successfully applied for the thermal decomposition modeling of ZnSO 4 [27], MgSO 4 [28] and potassium alum [57] reaction systems. shows the mass loss curves of pure ammonium sulfate from 25 to 500°C for three heating rates (10,15 and 20°C.min -1 ).…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…In industrial processes, the leach residue is generally not pure since it contains smaller amounts of other sulfates, such as iron, aluminum, and manganese. The decomposition of the eventually precipitated sulfates can be a route to obtain sulfur dioxide and metal oxides [27,28].…”
Section: Introductionmentioning
confidence: 99%